Estimation of individual and maternal additive genetic and heterotic effects for preweaning traits of crosses of Ayrshire, Brown Swiss and Sahiwal cattle in the lowland tropics of Kenya - Kahi, A.K.; Mackinnon, M.J.; Thorpe, W.R.; Baker, R.L.; Njubi, D. (Elsevier, 1995)
A total of 1443 records were used to estimate individual and maternal additive genetic breed and heterotic effects for preweaning growth and survival traits of crosses of Ayrshire (A), Brown Swiss (B), and Sahiwal (S) in a dairy herd in the lowland coastal tropics of Kenya. Individual and maternal additive genetic effects for A and S were not significant for any of the traits. Similarly, the individual heterotic effect of Bos taurus-B. indicus heterozygosity was not significant for calf performance. A small effect of AS individual heterosis on preweaning average daily gain (DG) was found. It was estimated that F1 AS calves gained 26 g/day faster than the mean of the purebred A and S. The maternal heterotic effect of B. taurus-B. indicus heterozygosity for birth weight (BW) was -3.19 +-1.25 kg and of opposite sign to estimates reported in the literature. The absence of any major variation among calf genetic groups showed that the individual and maternal breed and heterotic effects of the sire breeds and dam genotypes summed to give very similar aggregate preweaning performance for all traits except BW. Therefore no emphasis should be given to preweaning performance when selecting among these breeds and mating systems. Instead, breeding decisions aiming to increase herd productivity will be determined by relative lactation and reproductive performances of cows.